Types of Inherited Hemoglobin Disorders among the Patients Attending a Tertiary Care Hospital: Types of Inherited Hemoglobin Disorders among the Patients - Anwar, Rehan; Arzoo, Kamran; Riaz, Adnan; Ali, Riasat; Saghir, Sumera; Habib, Bilal (Pakistan Journal of Health Sciences, 2024)
The genetic conditions known as hemoglobinopathies, which include thalassemia impact the synthesis and structure of Hemoglobin, the red blood cell protein that carries oxygen. Objectives: To investigate the prevalence of different types of thalassemia associated with age, gender and Hematological parameters. Methods: The total number of participants was n=139. The cross-sectional study was conducted at Rai Medical College Sargodha. The study was conducted for six months, from July 2023 to Dec 2023. Biochemical parameters investigated such as Hemoglobin, mean corpuscular hemoglobin MCH, reticulocyte and ferritin were done in the Hematology lab. Collected data were analyzed by SPSS version 25.0. Results: The gender distribution among the participants included male 50.3% and female 49.6%. The mean age of the patients was approximately 34.8 years. This study of 139 participants found Hb-E Beta Thalassemia (25.4%) to be the most common type, especially among those with a history of cousin marriage. Severe forms like Hb-E Beta Thalassemia and Beta Thalassemia Major had low hemoglobin and MCH levels, indicating severe anemia, while milder forms showed near-normal levels. In mean corpuscular Hemoglobin E Beta Thalassemia (29.7 ± 4.1), p=0.001, mean corpuscular Hemoglobin A levels are considerably lower than Beta Thalassemia Trait. There was no association with age and gender, p>0.005. Conclusions: It was concluded that our investigation offered important insights into the biochemical profiles linked to various thalassemia types, even though it did not identify any appreciable variations in thalassemia prevalence by age or gender.